Comunicação e extensão na formação de um campo científico no Instituto Federal de Mato Grosso (Campus Cuiabá – Bela Vista) - Almeida, Thiago André de (2020)
In this work, we analyze the production of a scientific field at IFMT Campus Cuiabá – Bela Vista the extension activities, through which or institute has a greater impact on the internal public (documents and students) and external (surrounding community). The model of “communication as a culture” studies, which offers a dialogue with Social and Human Sciences, was chosen to adopt a perspective by the French sociologist Pierre Bourdieu, emphatically through field theory, associated with studies of public relations and organizational communication. The research makes use of the analysis of primary sources (diverse documents) and the bibliography referring to the creation of the IFMT Campus Cuiabá - Bela Vista in the expansion of the national network of technological education in the country. Despite its institutional youth, the Campus, according to changes in the profile of the faculty and in the production of teaching practices at various levels, has contributed to the expansion of scientific training in the municipality.